Contributions of Productivity and Relative Price Changes to Wheat Profitability Changes in China - Li Xiu-Shuang; Irfan Mir Chohan; Yu Kang (International Journal of Engineering and Management Research, 2021)
Using the provincial panel data of wheat from 1998 to 2018, based on the total price and quantity framework proposed by O'Donnell(2010), and using Färe-Primont productivity index, this artical decomposes the change of wheat profitability into the change of input-output relative price (TT) and the change of total factor productivity (TFP), and further decomposes the change of TFP into technological progress and efficiency change based on input orientation. The results showed that the overall profitability of wheat decreased by 24.9% compared with 1998, which was attributed to the decrease of TT by 32.6% and the increase of TFP by 11.4%. Results indicate that profitability change is mainly driven by TT change, and the impact of TT change on wheat profitability was alleviated by the compensatory change of TFP. The main driving factor of wheat TFP growth is technical progress, Compared with the growth of technical progress, the technical efficiency grows slowly.